Pengembangan Model Pembelajaran Interaktif Dengan Gaya Belajar Visual, Auditori, dan Kinestetik Pada Mata Pelajaran Informatika Untuk Siswa Kelas X MAN Batam - Basriadi, Ali; Devega, Army Trilidia; Sabtu, Sabtu; Suja’i, Iman (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
This learning model development research aims to produce an interactive learning model with visual, auditory and kinesthetic learning models using ADDIE development. When conducting interactive learning, a teacher needs to understand the characteristics and abilities of students. Students are no longer used as objects but are reduced to being polarized as students, pleasing students with learning styles according to their talents and abilities. The instrument uses a questionnaire assessing learning model experts, assessing media quality, material experts, informatics subject teachers, and student responses. The resulting model was tested on a small group in tenth grade. The average model expert assessment results were 4.093, material experts averaged 4.00, and media experts averaged 4.064, while the overall quality of learning media was 4.086 out of a total score of 5,000 which was included in the good category. The results of the model and media quality assessment were based on student responses with an average score of 3.252. And in the aspect of student interest and motivation in learning it was 3,366 with student learning completeness test results of at least 76%.Kata kunci: Gaya Belajar, Mata Pelajaran Informatika, Pengembangan Model, Visual, Auditori, dan Kinestetik